Fruits Program Area Research Planning and Prioritization: Background Analysis - Isabelita Pabuayon (Philippine Institute for Development Studies (PIDS), 2000)
This study addresses the Fruits Program Area research allocation concerns. It provides a background analysis focusing on the fruits industry profile, domestic and export potentials, supply constraints, role of public and private sector R&D, review of past agricultural research, technologies generated by the R&D program, constraints to and consequences of technology adoption, and the strengths and weaknesses in the institutional structure of research and extension linkage. Additionally, it provides suggestions on socio-economics research areas for integration in the overall fruits R&D agenda. The study involved (1) gathering and analysis of secondary (time-series) data from various sources (BAS, NSO, DTI) to come up with a profile of the fruit crops sector which covered the sectors economic contribution, production and yield performance, market potential, and constraints/problems affecting the industry; (2) extensive review of the literature on fruits in terms of research priorities by commodity (mango, banana, pineapple, citrus, durian, papaya, etc.), research area (varietal improvement, pest and disease control, cultural management, postharvest, socio-economics), institutions (SCUs, line agencies), budget, and current priorities; (3) examination of the national agricultural research system, the institutions involved in fruits RDE, networking mechanisms, and strengths and weaknesses of the RDE structure; and (4) consultations with informants from PCARRD, STARRDEC and STIARC, researchers, and a number of farmers. The list of researches on fruits obtained from DOST and reviewed in this study is certainly not complete but analysis have revealed important trends in fruits research priorities and budgetary allocation. Additional information obtained from PCARRD, UPLB and USM showed similar trends.
Keywords: 330; fruits industry; Obst; Obstbau; Obst- und Gemüsemarkt; Fruchthandel; Agraraußenhandel; Verarbeitung von Obst und Gemüse; Branchenentwicklung; Philippinen